Geokimia Batuan Beku Daerah Tanjung Kramat dan Sekitarnya, Kecamatan Hulonthalangi, Kota Gorontalo - Suwandi, Joga Bagaswicaksono; Kasim, Muh; Hutagalung, Ronal; Aris, Ayub Pratama (Journal of Applied Geoscience and Engineering, 2024)
The research area has a highly complex diversity of igneous rocks, predominantly consisting of fresh rocks, making it suitable for geochemical analysis. The research on the petrogenesis of igneous rocks is located in the Tanjung Kramat area and its surroundings, Hulonthalangi District, Gorontalo City. The aim of this research is to analyze the geological conditions of the study area, analyze magma affinity, and the tectonic setting of the formation of igneous rocks in the study area based on X-Ray Fluorescence (XRF) geochemical data. The methods required to achieve this research include observations of the geological conditions of the study area (lithological observations, outcrops, and rock sample collection), and laboratory analysis (XRF geochemical). The stratigraphy of the study area consists of four units, ordered from youngest to oldest, namely: alluvial deposit unit, limestone unit, porphyritic andesite unit, and granite unit. Geochemical analysis shows a tholeiitic magma affinity for the J.TK15 sample and calc-alkaline for the J.TK20 sample, with a tectonic setting of island arc calc-alkaline basalt, originating from a subduction zone or orogenic zone.